Automatic detection of vocalizations of the frog Diasporus hylaeformis in audio : 162nd Meeting of the Acoust. Soc. Am. San Diego, CA., November, 2011 - Camacho Lozano, Arturo (2011)
Resumen: Presenta un método capaz de reconocer las llamadas de la rana Diasporus hylaeformis bajo la presencia de ruido de fondo.